The Impact of IPPIS Policy on the University System: A Critical Assessment - Alhaji Hassan, Ndaliman; Manu, Hammadu; Ahmed, Mohammed (Kashere Journal of Politics and International Relations, 2023)
The 2020 industrial action embarked upon by the Academic Staff Union of Universities (ASUU) over the forceful enrolment of its members on the Integrated Payroll and Personnel Information System (IPPIS) by the federal government has elicited uncertainty on the stability of Nigeria`s university system. The paper examined the negative impact of the implementation of IPPIS on the Nigerian university system, as well as the overall implications of its rejection by ASUU on industrial harmony in Nigeria’s universities. The paper is premised on Marx`s Conflict Theory. Marx is of the view that human society is based on class relations, with opposing interests. The ruling class often imposes its rules to the detriment of the working class. Conflict is an inherent aspect of social relations, due to opposing interests. The study used secondary data and content analysis as its methodology. The paper found that the rationale behind the rejection of IPPIS by ASUU is that, IPPIS did not capture the peculiarities of Nigerian university` system, which include non-recognition of sabbatical and visiting lecturers, and non-recognition of payment of promotion arrears. More so, it negates the autonomy of the university system. The paper recommends that the federal government should accept the University Transparency and Accountability Solution (UTAS) proposed by ASUU which accommodates the peculiarities of universities in Nigeria.